2019
DOI: 10.1038/s41598-019-48520-7
|View full text |Cite|
|
Sign up to set email alerts
|

BTLA suppress acute rejection via regulating TCR downstream signals and cytokines production in kidney transplantation and prolonged allografts survival

Abstract: Acute rejection is a major risk for renal transplant failure. During this adverse process, activated T cells are considered the main effectors. Recently, B and T lymphocyte attenuator (BTLA), a member of the CD28 family receptor, was reported to be a novel inhibitory regulator of T cell activation in heart and pancreatic allograft rejection. Due to the similarity of acute rejection pathways among different organs, we hypothesized that BTLA might play a role in acute rejection of kidney transplant. In renal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
5
17
0
Order By: Relevance
“…First, the number of samples being screened for cox regression analysis is too small, only transcriptomics expression of BTLA with full clinical data was analyzed in this study. Second, cytokines not only carry information between tumors and immune cells but also be secreted by immune cells, playing an important role in TME ( Burkholder et al, 2014 ; Zhang J. et al, 2019 ). Cytokines-cytokines receptor interaction pathway is the top terms in KEGG analysis, but the role of BTLA in this pathway needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of samples being screened for cox regression analysis is too small, only transcriptomics expression of BTLA with full clinical data was analyzed in this study. Second, cytokines not only carry information between tumors and immune cells but also be secreted by immune cells, playing an important role in TME ( Burkholder et al, 2014 ; Zhang J. et al, 2019 ). Cytokines-cytokines receptor interaction pathway is the top terms in KEGG analysis, but the role of BTLA in this pathway needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Rat kidney transplantations were carried out according to a previously described procedure ( 26 ). Two experienced microsurgeons performed the surgeries in a sterile environment.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory effect of BTLA on the immune response has been confirmed by recent studies; for instance, targeted BTLA therapy can inhibit rejection in a mouse heart transplantation model ( 24 ) but less so in kidney transplantation. Our previous research has shown that the BTLA pathways were involved in the pathogenesis of AR in biopsy-proven recipients following kidney transplantation, and BTLA overexpression can suppress TCMR by regulating T cell receptor downstream signals ( 25 , 26 ). Additionally, several studies indicated the potential value of combining costimulatory or costimulatory molecules in disease treatment, which may reduce adverse effects through a lower single dose and provides new ideas for the prevention of kidney transplant rejection ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vital factors in T-cell signaling pathways, including mitogen-associated protein kinases (MAPKs), nuclear factor-kappa B (NF-κB), and nuclear factor of activated T cells (NFAT), are also significantly repressed by overexpression of BTLA. 39 The transcriptomic profile of ADAM12 −/− T cells strongly establishes that ADAM12 is a costimulatory molecule that cooperates with TCR signaling to trigger successful T-cell activation, proliferation, and Th1 cell fate and maintenance. ADAM12 −/− T cells are defective in inducing skin inflammation Next, we determined whether the transcriptomic profile of antigen-driven ADAM12 −/− T cells is associated with their capacity to establish inflammation and is stable in vivo, using the delayedtype hypersensitivity (DTH) T-cell-mediated inflammatory model.…”
Section: Transcriptomic Profiling Of Adam12 −/− T Cells Reveals Dysrementioning
confidence: 99%